2017
DOI: 10.1016/j.jagp.2016.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Delirium After Hip Fracture Surgery on One-Year Mortality in Patients With or Without Dementia: A Case of Effect Modification

Abstract: Objectives: We evaluated whether delirium after hip fracture repair modifies the relationship between baseline dementia and one-year mortality after surgery. Methods: Patients age ≥ 65 undergoing hip fracture repair surgery at John Hopkins Bayview Medical Center between 1999 and 2009 were eligible for this prospective cohort study. Baseline probable dementia was defined as either preoperatively-diagnosed dementia per geriatrician or < 24 on Mini Mental State Examination. Delirium was assessed using the Confu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 43 publications
0
30
1
2
Order By: Relevance
“…1 POD after hip fracture repair is associated with an increased likelihood of dependency in activities of daily living (ADLs) and instrumental activities of daily living (IADLs), 2,3 and a higher risk of not returning to pre-fracture level of mobility. 4 Furthermore, both duration of POD 5 and POD superimposed on dementia 6 are risk factors for mortality after surgery. Given the above, interventions which decrease POD have the potential to influence both functional and mortality outcomes.…”
Section: Editor's Key Pointsmentioning
confidence: 99%
“…1 POD after hip fracture repair is associated with an increased likelihood of dependency in activities of daily living (ADLs) and instrumental activities of daily living (IADLs), 2,3 and a higher risk of not returning to pre-fracture level of mobility. 4 Furthermore, both duration of POD 5 and POD superimposed on dementia 6 are risk factors for mortality after surgery. Given the above, interventions which decrease POD have the potential to influence both functional and mortality outcomes.…”
Section: Editor's Key Pointsmentioning
confidence: 99%
“…Four of the studies are prospective studies with a combined total of 1321 patients. Lee et al showed that patients with dementia had a higher risk of one year mortality than patients without dementia, with a hazard ratio of 1.71 (95% CI 1.06-2.77, P = 0.05) after adjusting for many variables such as age, sex, medical comorbidity and surgery duration [24]. Guerini et al showed that patients who were significantly older and had lower cognitive performance died at a higher rate during the 12-month period following discharge.…”
Section: Association Of Cognitive Impairment With Long-term Outcomesmentioning
confidence: 99%
“…Perioperative neurocognitive disorders (PND) have become the most common complications after routine surgical procedures, particularly in the elderly [1,2]. Following surgery (e.g., common orthopaedic procedures), up to 50% of patients experience cognitive disturbances that can lead to serious complications, including poorer prognosis and a higher 1-year mortality rate in subjects with pre-existing neurodegeneration [3]. Carotid artery stenosis (CAS) can be detected in 75% of men and 62% of women aged ≥65, with a stenosis extent of ≥50% occurring in 7% of men and 5% of women in this age group [4].…”
Section: Introductionmentioning
confidence: 99%